Urban trees as a lever for citizen engagement in public consultation processes: the case of Paris, France - Dakouré, Amélie; Georges, Jean-Yves (Frontiers in Sociology, 2024)
In the present context of increasing human population demography, worldwide social crises, and rapid ecological global change, large cities are facing major socio-environmental challenges. This convokes authorities to adapt their governance and urban planning to reconcile urban development, ecological systems, and city dwellers in the most sustainable way. To achieve such goals, local officials have to associate all local actors, including city-dwellers, to the decision-making process through participatory governance and/or participatory systems. Here, we elaborated an original pilot project governance system for a “Participatory System Combining Town Planning and Science” (the 2PS-CiTy), as part of the revision of the Local Urban Plan (LUP) of Paris, France, into a Bioclimatic LUP held from 2020 to 2024. By implementing 2PS-CiTy, we aimed to answer “How to turn trees into a lever for inhabitants’ engagement in urban consultation systems?” Trees were chosen because they are emblematic elements of nature with significant roles in ecosystemic services such as urban climate regulation. Parisians were invited to (i) share in the first questionnaire some information on their knowledge about the LUP and their engagement in it, (ii) identify urban trees they consider remarkable, (iii) explain their choice in a second questionnaire, (iv) contribute to the urban consultation as part of the LUP revision, and finally, (v) give their feedback during a dedicated survey. Out of the 41 Parisians who took part in 2PS-City, 83% declared they were motivated to participate because they could contribute to the tree census, which in turn can constructively contribute to the Parisian LUP revision to bring more nature and sustainability in town. This study demonstrates that trees can be used as a lever for inhabitants’ engagement in urban consultation systems to make cities more sustainable. Our survey also showed that the 2PS-CiTy governance system could be improved by (1) developing a participatory culture among decision-makers and (2) preventing nowadays silo governance from developing the most promising public governance systems that involve the departments of green space, urban planning, and local democracy.